Dominican Republic : Country Fiduciary Assessment, Volume 3, Country Procurement Assessment Report - Update - World Bank (Washington, DC, 2012)
The Dominican Republic has made significant strides in deepening democracy during the past decade including the implementation of an important electoral reform. This fiduciary assessment was prepared by the Bank and the Inter-American Development Bank (IDB) as a tool for their coordinated policy dialogue on governance with the country, and as a key input for their respective assistance strategies. Consequently, the report also provides important contributions to both institutions' analytical work on public sector management, and State modernization which will be the basis for developing these strategies jointly with the government. The report was prepared as a composite document summarizing the main procurement, and financial management issues identified by the two banks in the Dominican Republic, within the broader public sector management context. Several short-term actions recommended in Volume II Country Financial Accountability Assessment (CFAA) and Volume III Country Procurement Assessment Report (CPAR Update) address the problems linked to the Government's weak capacity to manage the fiduciary function. Volume I presents key public sector issues relevant for the financial management system, including systemic strengths and weaknesses, the political economy surrounding the State modernization effort, and the obstacles to, and incentives for public financial management reform. It provides a wider context which is useful to assess fiduciary reforms that can be realistically implemented and expected to achieve sustainable results. Volume I also fosters the integration of the main recommendations for broad systemic improvements relevant to the public financial management system. These include reducing discretion within the executive power, improving access to, and quality of information, working more effectively with civil society by tapping into the leading Civil Society Organizations' technical ability and capacity to form strong coalitions, and building upon ongoing reform efforts including, in particular, the Integrated Financial Management Project (SIGEF) supported by the IDB. These broad aspects are recommended as priority areas for reform because their successful implementation would contribute to lowering the systemic risks, and establishing an enabling environment for regulatory, and enforcement bodies to function effectively. Unless such conditions exist, the specific legal, and institutional reforms required to strengthen the procurement and financial management systems, even if implemented, are not likely to have significant impact on the overall quality of public sector management.